"I Just Want to Finish High School like Everybody Else": Continuation High School Students Resist Deficit Discourse and Stigmatization. Issue 4 (2nd October 2019) - Sperling, Jenny
ABSTRACT: Alternative education provides different and powerful opportunities for learning. In this article, the author focuses on students who resist stereotypes that are produced and maintained by dominant powers and ideologies, and who share their knowledge and experiences with systemic marginalization. Drawing from classroom videos, qualitative interviews, and a class-produced YPAR project, the author highlights the experiences of ten continuation high school students who speak back to the deficit framing of alternative education students. The students' research project, which is now a public video documentary, has implications for school accountability reformers, educators, and practitioners.